ANALISIS PEMECAHAN MASALAH MATEMATIKA MENURUT POLYA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Irawanti, Ida; Hariyani, Sri; Suwanti, Vivi (SIGMA, 2024)
This study focuses on discussing the result of the analysis of (1) the ability to solve mathematical problems of SPLDV material based on Polya, (2) the causes of student errors in solving mathematical problems of SPLDV material. This research is qualitive research and the type of research is qualitive-exploratory. The subject in this study were class X student of SMK Bina Kartika Nusantara Tirtoyudo. Data collection procedures observations, through tests, interviewers, and documentation. Data is analyzed qualitatively including data reduction, data presentations, and drawing conclusions. Checking the validity of the data is carried out by triangulation. The test results from this study show that there are 3 excellent  criteria, there are  4  good criteria, there   are 5  students  , and The criteria are  less than 3 students.  The causes of student errors   in this study are forgetting or not remembering formulas, difficulty understanding symbols that cause work and  the final result is not just right. The conclusion of  this study is that students  with high categories are able to meet all indicators including understanding problems, planning solutions, implementing solutions  and rechecking.   Learners with a moderate category are only able to meet the  indicators of understanding the problem, planning the solution  and carrying out the solution. Learners with low categories  are only able to understand the problem and plan for a solution.